Access to therapy services for people with disability in rural Australia: a carers' perspective. (17th October 2016) - Gallego, Gisselle; Dew, Angela; Lincoln, Michelle; Bundy, Anita; Chedid, Rebecca Jean; Bulkeley, Kim; Brentnall, Jennie; Veitch, Craig
Abstract: In Australia and around the world, people with disability and their carers living in rural areas face additional challenges compared to their urban‐dwelling counterparts. This cross‐sectional study explored current access to therapy services for people with disability living in western New South Wales as reported by their primary carers. Data were collected using an online and paper survey distributed to carers, from December 2012 until June 2013. Information was sought about the carers, the person they care for, access to physiotherapy, speech pathology, occupational therapy and psychology services. A total of 166 carers participated. Respondents were mostly the carers of a son or daughter (83.6%), the person they care for had an average age of 17.6 years (range 1–69 years) and more than half were males (56%). The majority of people with disability (73.5%) had received therapy services in the last 2 years. Waiting time and distance travelled to access physiotherapy, speech and occupational therapy services varied. People with disability had to wait an average of 6.6 months to receive speech pathology and had to travel an average of 2.6 hours to receive physiotherapy. The main provider of all services was the specialist disability government department, except for psychology, which is mainly provided in the private sector. From the carers' perspective, availability and accessibility to services are limited. Carers noted that availability of services was more restricted once people with disability reached adulthood. Lack of choice and frustration with the lack of availability of specialist disability services was reported frequently. Carers believed that timely allied health intervention prevented the development of more severe or complicated conditions that had a greater impact on carers, families, communities and the person with disabilities.